Quality control study of hospital laundry in a tertiary care hospital - Kiran Gopal; Shivakumar S. Solabannavar (Tropical Journal of Pathology and Microbiology, 2019)
Introduction-Hospital laundry are potential reservoirs of bacteria in hospitals. Preventing contamination and providing clean linen and laundry should help to prevent hospital acquired infections. Being an important component in the management of patients and the role in causing hospital acquired infections, the study about hospital laundry has been undertaken in our hospital.Methods- Quality control practiced in the Linen and Laundry Service was studied by conducting a prospective study. Samples were taken from the surface of these materials by sweep plate method prior to washing procedure. The second set of samples were collected from the same materials after the washing procedure. The organisms were identified by colony morphology, culture characteristics & biochemical reactions according to standard techniques.Results- Out of the 30 samples studied, 24 (80%) of them were contaminated with bacteria before washing. Organisms yielded were Staphylococcus aureus, coagulase negative Staphylococcus (CONS), Aerobic spore bearing bacilli (ASB), Escherichia coli and Pseudomonas aeruginosa. After washing, 25 (83%) of the clothes were sterile.Conclusion- Though terminal cleaning fails to completely eliminate bacteria from the laundered fabrics, it is effective in considerable reduction in bacterial growth.